Social marketing and asset mapping: tools for the challenges of community health promotion - Yolanda Patricia Moncayo Sánchez; Marlene Jacqueline García Veloz; Marcia Verónica García Veloz; Edwin Marcelo Jijón Paredes (Revista Habanera de Ciencias Médicas)
Introduction: In the current context, where health systems face significant pressures arising from demographic changes, the increase in chronic diseases and social inequalities, health promotion, with the use of social marketing and asset mapping, is emerging as a key resource to address these challenges.